LPA Gene, Ethnicity, and Cardiovascular Events. Issue 3 (17th January 2017) - Lee, Sang-Rok; Prasad, Anand; Choi, Yun-Seok; Xing, Chao; Clopton, Paul; Witztum, Joseph L.; Tsimikas, Sotirios
Abstract : Background: The relationship of LPA single nucleotide polymorphisms (SNPs), apolipoprotein(a) isoforms, and lipoprotein(a) [Lp(a)] levels with major adverse cardiovascular events (MACE) in different ethnic groups is not well known. Methods: LPA SNPs, apolipoprotein(a) isoforms, Lp(a), and oxidized phospholipids on apolipoprotein B-100 (OxPL-apoB) levels were measured in 1792 black, 1030 white, and 597 Hispanic subjects enrolled in the Dallas Heart Study. Their interdependent relationships and prospective association with MACE after median 9.5-year follow-up were determined. Results: LPA SNP rs3798220 was most prevalent in Hispanics (42.38%), rs10455872 in whites (14.27%), and rs9457951 in blacks (32.92%). The correlation of each of these SNPs with the major apolipoprotein(a) isoform size was highly variable and in different directions among ethnic groups. In the entire cohort, Cox regression analysis with multivariable adjustment revealed that quartiles 4 of Lp(a) and OxPL-apoB were associated with hazard ratios (95% confidence interval) for time to MACE of 2.35 (1.50–3.69, P <0.001) and 1.89 (1.26–2.84, P =0.003), respectively, versus quartile 1. Addition of the major apolipoprotein(a) isoform and the 3 LPA SNPs to these models attenuated the risk, but significance was maintained for both Lp(a) and OxPL-apoB. Evaluating time to MACE in specific ethnic groups, Lp(a) was a positive predictor and the size of the major apolipoprotein(a) isoform was an inverse predictor in blacks, the size of the major apolipoprotein(a) isoform was an inverse predictor in whites, and OxPL-apoB was a positive predictor in Hispanics. Conclusions: The prevalence and association of LPA SNPs with size of apolipoprotein(a) isoforms, Lp(a), and OxPL-apoB levels are highly variable and ethnicity-specific. The relationship to MACE is best explained by elevated plasma Lp(a) or OxPL-apoB levels, despite significant ethnic differences in LPA genetic markers. Abstract : Supplemental Digital Content is available in the text.